Effects of adding cocoa fermentation medium on cigar leaves in agricultural fermentation stage - Zong, Pengfei; Hu, Wanrong; Huang, Yang; An, Hongyue; Zhang, Qianying; Chai, Zhishun; Lei, Yun Kang; Wang, Jun; Li, Dongliang; Cai, Wen (Frontiers in Bioengineering and Biotechnology, 2023)
With the development of the world economy and the integration of cultures, the Chinese cigar market has shown a significant upward trend. However, high-quality cigar leaves are mostly produced in Dominica, Cuba, Nicaragua and other places. In contrast, Chinese cigar leaves have problems such as insufficient aroma, which has become one of the main factors restricting the development of Chinese cigars. Adding medium to ferment is a traditional method in the cigar industry. At present, it mostly relies on manual experience, and lacks systematic and scientific research. At the same time, the addition of medium fermentation is mainly concentrated in the industrial fermentation process, and has not yet begun to be applied in the agricultural fermentation process. In this study, the medium was added to the agricultural fermentation process for the first time to explore the possibility of the application. The effects of adding cocoa medium to ferment on the chemical composition, sensory quality and surface microbial diversity of eggplant core cigar leaves were investigated.wrapper [Method] With ' Dexue 7 ' as the experimental material, the changes of main chemical components of wrapper fermented with water and cocoa medium were determined, and microbial community structure on the surface and relative abundance of cigar leaves at different turning periods were analyzed, and the functional genes were predicted. The results of the study were as follows: 1) The results of sensory evaluation showed that the addition of cocoa medium could highlight the aroma of bean, cocoa and coffee, improve the sweetness and fluency and the combustibility of cigar leaves.2) The addition of cocoa medium increased the contents of proline and malic acid which were positively correlated with sensory quality, and decreased the contents of citric acid, linoleic acid, basic amino acids and aromatic amino acids which were negatively correlated with sensory quality. 3) The addition of cocoa medium increased the total amount of aroma components in cigar leaves, especially carotenoid degradation products, and changed the structural composition of some aroma substances in wrappercigar leaves.4) The similarity of species composition between the water-added group and the cocoa-added group was higher.